EFEKTIVITAS EKSTRAK BUAH SAWO, BAWANG PUTIH, DAUN ANDONG, DAN BUAH PARE TERHADAP PERTUMBUHAN BAKTERI ESCHERICHIA COLI - Susiwati, Susiwati (JURNAL MEDIA KESEHATAN, 2014)
This research aims to determine the inhibition of sapodilla fruit, garlic, andong leaves and pare fruit toward the growth of escherichia coli bacteria. Antimicroba test used paper disc diffusion was in-vitro test. Sapodilla fruit, garlic, andong leaves and pare fruit were extracted by using maceration process. The extracts were tested on the growth of E- coli bacteria. The highest inhibition zone (6,7mm) was found in andong leaves extract. The highest inhibition zone was 8.3 mm, whereas the inhibition of pare fruit did not not provide the inhibitory zone. It can be concluded that garlic extract, sapodolla extract and decoction of andong leaves have highly inhibitory in vitro. Based on stastistical analysis, there was Significant difference betwen the effectiveness of garlic extract with a decoction of andong leaves but the effectivess of garlic extract with sapodilla extract was not meaningful. Whereas pare fruit did not give any inhibition zones. From the result of this research, the society can be encouraged to consume andong leaves or sapodilla fruit to treat diarrhea. In addition, garlic spices and pare fruit also can be used to overcome diarrhea, which is caused by the bacterium E. coli.